1995
DOI: 10.2172/10120351
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of potassium iodide (KI) prophylaxis for the general public in the event of a nuclear accident

Abstract: A generic difficulty encountered in cost-benefit analyses is the quantification of major elements that define the costs and the benefits in commensurate units. In this study, the costs of making KI available for public use, and the avoidance of thyroidal health effects predicted to be realized from the availability of that KI (i.e., the benefits), are defined in the commensurate units of dollars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…where Qu is the initial concentration of iodide in plasma in µg /100mL, and while (Behling, 1995) suggests T1/2=5h, it is seems better to adopt 6 hours, doing so the time varying transfer rate coefficients obtained in previous works (Jang et al, 2008) can be well reproduced, as shown in Figure 2. This half-life can also be derived considering the 3-compartements model and an exponential fit for the iodide in blood (data not shown).…”
Section: "'Standard" Biokinetic Model (Without Ki Administration)mentioning
confidence: 69%
See 1 more Smart Citation
“…where Qu is the initial concentration of iodide in plasma in µg /100mL, and while (Behling, 1995) suggests T1/2=5h, it is seems better to adopt 6 hours, doing so the time varying transfer rate coefficients obtained in previous works (Jang et al, 2008) can be well reproduced, as shown in Figure 2. This half-life can also be derived considering the 3-compartements model and an exponential fit for the iodide in blood (data not shown).…”
Section: "'Standard" Biokinetic Model (Without Ki Administration)mentioning
confidence: 69%
“…Then, the thyroid progressively eliminates the stable iodide and the blood-to-thyroid transfer rate increases accordingly, until it reaches the standard value given in Table 1 again. The time equation of iodide concentration in blood is given by (Behling, 1995):…”
Section: "'Standard" Biokinetic Model (Without Ki Administration)mentioning
confidence: 99%